Tingkat Kepuasan Petani Terhadap Kelompok Tani Sentra Bawang Merah di Kabupaten Situbondo - Desi Komalasari; Joni Murti Mulyo Aji; Rokhani Rokhani (Universitas Galuh, 2026)
The horticultural sub-sector particularly shallots being one of Indonesia’s key commodities. Situbondo Regency is one of the main shallot production centers in East Java that contributes substantially to regional output. However, the effectiveness of farmer groups in improving productivity and farmer welfare has not yet reached optimal levels, as indicated by the decline in harvested area and production volume over the past two years. This research aimed to: (1) analyze the role of farmer groups in improving the production efficiency of shallot farming in Situbondo Regency, (2) assess the level of farmer satisfaction with farmer groups in the shallot production centers, and (3) analyze the relationship between the role of farmer groups and the level of farmer satisfaction. The study employed a descriptive quantitative method using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) approaches. The results showed that: (1) farmer groups play a positive role in enhancing production efficiency, particularly in the provision of farming inputs and the adoption of cultivation technologies; (2) the level of farmer satisfaction with the farmer groups was categorized as “moderately satisfied,” with a CSI score above 60%, where aspects requiring improvement include transparency in management and market access; and (3) there is a significant relationship between the effectiveness of farmer group roles and farmer satisfaction levels. The more active the group’s role in facilitating cooperation and providing guidance, the higher the farmers’ satisfaction toward the group’s performance.